Conjugate observations of traveling convection vortices associated with transient events at the magnetopause. Issue 3 (28th March 2015) - Kim, H.; Clauer, C. R.; Engebretson, M. J.; Matzka, J.; Sibeck, D. G.; Singer, H. J.; Stolle, C.; Weimer, D. R.; Xu, Z.
Abstract Traveling convection vortices (TCVs) are generally produced by field‐aligned currents (FACs) at high latitudes associated with transient changes of the magnetopause. This paper presents multipoint conjugate observations of transient events at the magnetopause measured in space and on the ground. The transient events showing radial fluctuation of the magnetopause in association with sudden increases in solar wind dynamic pressure were detected by both the Time History of Events and Macroscale Interactions during Substorms and the Geostationary Operational Environmental Satellite spacecraft. Geomagnetic signatures seen as TCVs in response to the transient events were observed by the ground magnetometer array in Greenland and Canada and their conjugate locations in Antarctica including recently developed Antarctic magnetometers, mostly located along the 40° magnetic meridian. This new conjugate network provides a unique opportunity to observe geomagnetic field signatures over a relatively large region in both hemispheres. This study focuses mainly on the spatial and temporal features of the TCVs in the conjugate hemispheres in relation to the transient events at the magnetopause. The TCV events are characterized by their single or twin vortex, of which the centers are located approximately at 72°–76° magnetic latitude, propagating either dawnward or duskward away from local noon. While interhemispheric conjugacy is expected with an assumption that TCV signatures are created by FACs directed in both hemispheres, our observations suggest that there might be more complex mechanisms contributing the asymmetrical features, perhaps due to field line mapping and/or conductivity differences.